THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY AND CUSTOMER SATISFACTION AS MEDIATOR VARIABLE IN PT. BANK MANDIRI (PERSERO) TBK, BRANCH TANJUNGPURA PONTIANAK - B12111021, R. Haryo Briantoro_ (Jurnal Manajemen Update, 2015)
This study aims to determine the influence of CRM towards customer satisfaction and customer loyalty. The research method used in this research is quantitative research methods, the research objects are Customers of Bank Mandiri Tanjungpura Pontianak with sample 100 respondents. Data was collected by questionnaire. This research use path analysis to analyze the data.The result shows that Variable technology has a positive and not significant influence towards customer satisfaction, and also has a positive and significant influence on customer loyalty. Variable people have a positive and not significant influence towards customer satisfaction, and also have a positive and significant influence towards customer loyalty. Variable process has positive and significant influence towards customer satisfaction, and also has a positive and not significant influence towards customer loyalty. Variable customer satisfaction has positive and significant influence towards customer loyalty.Keywords: CRM, technology, people, process, customer satisfaction, customer loyaltyINTRODUCTION